Effects of the narrative elaboration technique and open-ended rapport on accuracy of children’s recall according to age - Lee, Seungjin; Shin, Minkyeong (Frontiers in Psychology, 2025)
IntroductionThis study explored the impacts of the narrative elaboration technique (NET) and open-ended rapport building on younger (n = 30, ages 5–6) and older (n = 30, ages 7–8) children’s free recall and suggestibility.MethodsChildren were randomly assigned to either a NET condition or an open-ended rapport condition after engaging in a photo-taking play session with an experimenter. Then, a novel interviewer asked them about the play session. The effects of the experimental conditions on children’s free recall and suggestibility were examined according to children’s age groups.ResultsResults revealed that open-ended rapport played a more significant positive role in young children’s free recall and suggestibility when compared to NET. No significant differences were observed in the effects of NET and open-ended rapport on older children’s memory performance.DiscussionPractical guidance is provided in terms of prioritizing open-ended rapport over NET to maximize young children’s spontaneous and accurate recall.